The effect of plugging of tubes on failure of shell and tube heat exchanger. (October 2019) - Farrahi, G.H.; Chamani, M.; Kiyoumarsioskouei, A.; Mahmoudi, A.H.
Abstract: In shell and tube heat exchangers, deep cracks can occur in tube-to-tubesheet welding and repairing such cracks is an impossible task which makes these tubes totally out of service. To preserve the thermal and mechanical integrity of heat exchanger, a series of rods is passed through these tubes and then are welded to tubesheets from both ends. Due to the increased damages in the vicinity of plugged tubes, the effect of plugging the tubes in the surrounding tubes and tubesheet failure is investigated. To this end, using CFD analysis, the temperature and pressure were calculated throughout the heat exchanger and then, the deformations and stresses of the tubes and tubesheets were computed using uncoupled thermo-mechanical analysis. The results of the research showed that by plugging the tubes, the plastic strain around them increases significantly and the possibility of crack formation in the surrounding tubes would be highly likely. Consequently, plugging the tubes should be considered as a temporary repair. Graphical abstract: Unlabelled Image Highlights: CFD and FEM analysis were used to investigate the nature of failure in a petrochemical heat exchanger. Temperature of the inner surface of the tubes was increased 15°C by plugging 15% of tubes. Increases the possibility of crack formation in the surrounding tubes by plugging the tubes. Dense distribution of plugged tubes resulted in higher plastic strain in adjacent tubes. Plugging the tubes should be considered as a temporary repair.